History of the musical instrument found in the town of Bidayik-Asar (2nd-4th centuries C.E.) - Tazhekeyev, Әзілхан; Zhakisheva , Зәбира (Turkic Studies Journal, 2024)
The article examines fragments of wooden musical instruments found by the Horezm Archaeological and Ethnographic Expedition (HAEE) at the Bidayik-Asar monuments associated withthe Zhetyasar culture, which developed in the eastern Aral Sea region. The HAEE began its initial archaeological investigations of the Zhetyasar sites in 1946 with subsequent expeditions in 1948, 1949, and 1951, under the leadership of S.P.Tolstoy. These excavations led to the identification of the ‘Zhetyasar Culture’. These field research continued into the 1970s and 1980s. Findings from the 1970s–1980s indicate that Bidayik-Asar was inhabited during the first half of the first millennium CE. Based on these dates, the musical instruments found at the site are classified among the earliest known wooden stringed instruments. This discovery, of great scientific interest to music archaeologists, has been categorized into several groups of musical instruments which are currently undergoing detailed study. The design of the instruments suggests that they may represent early imitations of stringed instruments, crafted from wood.The other part of the bodywork, with opened top and bottom, indicates the existence of different types of musical instruments. Several hypotheses have been proposed to explain their origin and use.